Religiously fashionable: constructing identity of urban muslimah in Indonesia - Fakhruroji, Moch; Rojiati, Umi (Penerbit Universiti Kebangsaan Malaysia, 2017)
The rise of hijabers community in various major cities in Indonesia has led to a new identity of Muslimah (Muslim women) in urban areas. By focusing on Hijabers Community Bandung (HCB), this paper outlines the facts about how this community responds to modernity and globalization in a positive way by creating its own global tastes. The inventions of styles those adjusted with the Islamic values generally showed the phenomenon of hijab transformation as a symbol of modernity which was implicated in the emergence of new identities of urban Muslimah. Using participant observation and in-depth interview, this study reveals several things, among others; First, HCB members have attempted to construct their identity by means of legitimizing identity, resistance identity and projecting identity. Second, HCB proves that their existence is not only manifested through the appearance, but also the implementation of a number of socio-religious activities. Third, HCB demonstrates that wearing hijab is part of a symbolic communication over ideological identity, community affiliation, and social status. In general, the identity of urban Muslimah that constructed by HCB are those are accommodated modern culture without leaving their identity as Muslimah.